Students' Cultural Literacy Development through Dialogical Approach in Senior High School - Rizal, Awaludin; Nursalim, Nursalim; Ajam, Ali; Lestari, Sri Ayu Budi; Ridayani, Ridayani (KnE Social Sciences, 2024)
The aim of this study is to evaluate the efficacy of the dialogical approach in developing students’ cultural literacy in senior high school. A quasi-experiment method with a non-equivalent control group design was employed in this research, with an experimental class and a control class. Descriptive analysis and prerequisite tests, such as homogeneity and normality tests, were used in this study’s data analysis techniques. Additionally, the Independent Sample T-Test and N-Gain data analysis were used to test hypotheses. The findings of this study demonstrate that implementing the dialogical approach can significantly enhance students’ cultural literacy, with a notable difference in efficacy between the experimental and control groups in second-grade students of senior high school. The study’s findings are worldwide diversity character data gathered using 30-item questionnaire as a research tool. After receiving the treatment, the average posttest findings demonstrate that students’ understanding of global variety has improved, particularly in the experimental group. The average posttest score for the experimental class was 91.46, whereas the control class’s score was 71.37. This indicates that the experimental class’s posttest score was higher than the control class’s. This demonstrates that the experimental class’s worldwide variety is greater than the control class’s. The practical implication of students’ cultural literacy in the classroom and school environment is the ability to understand and accept differences in cultural diversity backgrounds among them. Thus, the nation’s integrity and unity can be achieved according to the ideals of the state. Of course, the authors have limitations in this study.Therefore, in the future, input and further research are needed in order to perfect the results of previous research results. Keywords: cultural Literacy, dialogical Approach, students development skill